Lower stratospheric gravity wave activity over Gadanki (13.5°N, 79.2°E) during the stratospheric sudden warming of 2009: Link with potential vorticity intrusion near Indian sector - Nath, D.; Sridharan, S.; Sathishkumar, S.; Gurubaran, S.; Chen, W. (My University, 2013)
The relation between intrusions of stratospheric air into the upper troposphere and deep convection at equator during the stratospheric sudden warming (SSW) event of 2009 is examined using the ERA-interim reanalysis and NOAA outgoing longwave radiation (OLR) data sets. There is an intrusion of potential vorticity (PV) equatorward and westward, when the amplitude of planetary wave of zonal wavenumber 2 at 10 hPa decreases drastically and polar stratospheric temperature increases simultaneously at 60°N. As a special case, the PV intrudes as narrow tongue at longitudes near 60°E (Indian ocean sector) even to latitudes less than 20°N during the SSW, whereas PV normally intrudes near 210°E (eastern Pacific) to equatorial latitudes. Decrease in OLR is observed east of these PV intrusions. Vertical velocity is largely upward at all pressure levels. As the PV intrusion can have profound influence on tropospheric convection and the latent heat release due to equatorial convection is an important source mechanism for the generation of gravity waves, we examined gravity wave activity in the daily radiosonde observations of winds and temperature at Gadanki (13.5°N, 79.2°E). It is observed that the potential energy per unit mass, estimated from the gravity wave temperature perturbations has considerably enhanced in relation with the deep convection. The predominant direction of propagation of the gravity waves is westward prior to the SSW, as a response to the active convection over Indonesia, turns to eastward during and after the SSW, as a response to the PV intrusion induced convection over west of India.
Keywords: Stratospheric sudden warming; Potential vorticity; Gravity waves; Deep convection; SSW